2014
DOI: 10.1007/s13197-014-1432-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein concentrates, emulsifiers on textural and sensory characteristics of gluten free cookies and its immunochemical validation

Abstract: The effect of 5, 7.5 and 10 % protein concentrates namely soya protein isolate (SPI), whey protein concentrate (WPC) and addition of 0.5 % emulsifiers such as glycerol monostearate (GMS), sodium stearoyl- 2- lactylate (SSL) and lecithin (LEC) on the rheological, sensory and textural characteristics of cookies with rice flour and its immunochemical validation was studied. The results showed that the use of 7.5 % SPI/WPC along with GMS significantly improved the quality characteristics of cookies with rice flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…Sarabhai et al . (), who added up to 10% whey protein, also observed that a * values increased and b * values decreased when increasing the amount of protein. The differences between cookies with GP and HGP may be due to the way in which proteins affect Maillard reactions, which are responsible for the cookie colour, as discussed previously.…”
Section: Resultsmentioning
confidence: 84%
“…Sarabhai et al . (), who added up to 10% whey protein, also observed that a * values increased and b * values decreased when increasing the amount of protein. The differences between cookies with GP and HGP may be due to the way in which proteins affect Maillard reactions, which are responsible for the cookie colour, as discussed previously.…”
Section: Resultsmentioning
confidence: 84%
“…Schober et al (2003) added starches in gluten-free cookies formulations but they were mixed with three gluten-free flours and only three mixtures were analysed, therefore the effect of starches could not be clearly compared. Sarabhai et al (2015) studied the effect of protein concentrate (soya and whey protein), however they were added with emulsifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Gluten-free cookies formulation without any improver (isolated soy protein and hydrocolloids) were reported to increase the cookies hardness significantly [11,12]. Our preliminary research also showed that the substitution of wheat flour 100% to mocaf without the addition of isolated soy protein and hydrocolloid resulted in increasing hardness of cookies texture [8].…”
Section: Physical Analysismentioning
confidence: 63%